Hubungan asupan zat gizi makro, kualitas tidur dan aktivitas fisik dengan status gizi pada karyawan shift di PT. Pajitex - Qonita Amalia Zulfa; Endo Dardjito; Teguh Jati Prasetyo (University of Darussalam Gontor, 2022)
Background : Good work productivity can not be separated from the lifestyle of workers. Unhealthy lifestyle can have an impact on the employee’s nutritional problem. This study aims to determine the relation between macronutrient intake, sleep quality, and physical activity with the nutritional status of shift employees at PT. PAJITEX Pekalongan Regency. Method : This study used a cross sectional study design with a total sample of 87 employees selected by purposive sampling technique. Nutrient intake variables was measured used a recall 2x24 hour, sleep quality used the Pittsburgh Quality Sleep Index (PSQI) questionnaire, physical activity used the Global Physical Activity Questionnaire (GPAQ) and nutritional status used Body Mass Index (BMI). Data analysis used Korelasi Pearson correlation and multiple linear regression tests. Result : There was a relation between energy intake (p=0,000 r=0,392), protein (p=0,000 r=0,415), fat (p=0,000 r=0,393), carbohydrates (p=0,000 r=0,450), sleep quality (p=0.046 r=0,215) and physical activity (p=0.000 r=-0,406) with nutritional status. Multiple linear regression tests showed that there was an effect of macronutrient intake, sleep quality and physical activity together (p=0,000) with nutritional status of 39,2%. Conclusion : There was a relationship between macronutrient intake, sleep quality and physical activity with nutritional status.AbstrakLatar Belakang : Produktivitas kerja yang baik tidak terlepas dari gaya hidup pekerja. Gaya hidup yang tidak sehat dapat berdampak pada masalah gizi pekerja. Penelitian ini bertujuan untuk mengetahui hubungan asupan zat gizi makro, kualitas tidur dan aktivitas fisik dengan status gizi pada karyawan shift di PT. PAJITEX Kabupaten Pekalongan. Metode : Penelitian ini menggunakan desain cross sectional study dengan jumlah ampel sebesar 87 karyawan yang dipilih dengan teknik purposive sampling. Variabel asupan zat gizi diukur menggunakan recall 2x24 jam, kualitas tidur dengan kuesioner Pittsburgh Quality Sleep Index (PSQI), aktivitas fisik dengan Global Physical Activity Questionnaire (GPAQ) dan status gizi dengan Indeks Massa Tubuh (IMT). Analisis data menggunakan korelasi Korelasi Pearson dan uji regresi linear berganda. Hasil : Terdapat hubungan asupan energi (p=0,000 r=0,392), protein (p=0,000 r=0,415), lemak (p=0,000 r=0,393), karbohidrat (p=0,000 r=0,450), kualitas tidur (p=0,046r=0,215) dan aktivitas fisik (p=0,000 r=0,406) dengan status gizi. Uji regresi linear berganda menunjukkan terdapat pengaruh asupan zat gizi makro, kualitas tidur dan aktivitas fisik secara bersama-sama (p=0,000) dengan status gizi sebesar 39,2%. Kesimpulan : Terdapat hubungan asupan zat gizi makro, kualitas tidur dan aktivitas fisik dengan status gizi.